The Impact of Digital Technology on the Management of Educational Resources in Pandeglang Regency - Ikhwan, Khairul; Hanifah, Umi; Basrowi; Mutoharoh , Mutoharoh; Ali Yusuf, Furtasan; Umalihayati (Southeast Asian Journal of Science and Technology, 2025)
This study aims to analyze the impact of the implementation of digital technology on the management of educational resources in Pandeglang City. Using a quantitative approach with a descriptive design, this study involved 10 schools that have implemented digital technology in managing administration, human resources, educational facilities, and academic data. The results show that the implementation of digital technology significantly improves the efficiency and effectiveness of educational resource management, with the greatest improvement seen in administration and academic data management. However, challenges related to infrastructure limitations and training need to be addressed to maximize the benefits of digital technology. Therefore, strengthening technological infrastructure and increasing training for educators and administrative staff are key factors in ensuring the successful implementation of digital technology in schools in Pandeglang City.